Draft Genome and Complete Hox-Cluster Characterization of the Sterlet (Acipenser ruthenus) - Cheng, Peilin; Huang, Yu; Du, Hao; Li, Chuangju; Lv, Yunyun; Ruan, Rui; Ye, Huan; Bian, Chao; You, Xinxin; Xu, Junmin; Liang, Xufang; Shi, Qiong; et al. (Frontiers in Genetics, 2019)
Background: Sturgeons (Chondrostei: Acipenseridae) are a group of “living fossil” fishes at a basal position among Actinopteri. They have raised great public interest due to their special evolutionary position, species conservation challenges, as well as their highly-prized eggs (caviar). The sterlet, Acipenser ruthenus, is a relatively small-sized member of sturgeons and has been widely distributing in both Europe and Asia. In this study, we performed whole genome sequencing, de novo assembly and gene annotation of the tarlet to construct its draft genome. Findings: We finally obtained a 1.83-Gb genome assembly (BUSCO completeness of 81.6%) from a total of 316.8-Gb raw reads generated by an Illumina Hiseq 2500 platform. The scaffold N50 and contig N50 values reached 191.06 and 18.88 kb, respectively. The sterlet genome was predicted to be comprised of 42.84% repeated sequences and to contain 22,184 protein-coding genes, of which 21,112 (95.17%) have been functionally annotated with at least one hit in public databases. A genetic phylogeny demonstrated that the sterlet is situated in the basal position among ray-finned fishes and 4dTv analysis estimated that a recent whole genome duplication occurred 21.3 million years ago. Moreover, seven Hox clusters carrying 68 Hox genes were characterized in the sterlet. Phylogeny of HoxA clusters in the sterlet and American paddlefish divided these sturgeons into two groups, confirming the independence of each lineage-specific genome duplication in Acipenseridae and Polyodontidae. Conclusions: This draft genome makes up for the lack of genomic and molecular data of the sterlet and its Hox clusters. It also provides a genetic basis for further investigation of lineage-specific genome duplication and the early evolution of ray-finned fishes.